Barbara McClintock - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Chin, Mei Lee; Norhayati, Nordin; Siti Aisah, Harun; Nenie Zuryati, Abdullah; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras (Penerbit Universiti Malaysia Pahang, 2011)
Barbara McClintock (June 16, 1902 - September 2, 1 the 1983 Nobel Laureate in Physiology or Medicine, wa an American scientist and one of the world's most distinguished cytogeneticists.